2017
DOI: 10.3103/s1067821217010059
|View full text |Cite
|
Sign up to set email alerts
|

Application of combined casting–pressing for the fabrication of aluminum wire for soldering waveguides

Abstract: Сибирский федеральный университет (СФУ), г. КрасноярскСтатья поступила в редакцию 09.11.15 г., подписана в печать 25.11.15 г. Рассмотрены технические и технологические особенности схемы получения проволоки из литейных алюминиевых спла-вов, предназначенной для пайки волноводов, с использованием процесса совмещенного непрерывного литья-прессова-ния цветных металлов. Установлены зависимости, необходимые и достаточные для проектирования конструктивных элементов оборудования и технологических режимов, обеспечива… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…As studies of the methods of continuous extrusion of metals have shown [15][16][17][18][19][20][21][22][23][24], their use significantly increases the efficiency of the production of profiles from non-ferrous metals. One of the promising directions in the development of these technologies is the combination of continuous casting with extrusion on a Conform installation with a horizontal carousel mold [21][22][23][24][25][26]. During the operation of the installation, the metal melt is fed through the batcher into the annular groove of the rotating mold wheel and solidifies to contact with the stationary part of the container, formed at the interface of the groove with the arcuate segment (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…As studies of the methods of continuous extrusion of metals have shown [15][16][17][18][19][20][21][22][23][24], their use significantly increases the efficiency of the production of profiles from non-ferrous metals. One of the promising directions in the development of these technologies is the combination of continuous casting with extrusion on a Conform installation with a horizontal carousel mold [21][22][23][24][25][26]. During the operation of the installation, the metal melt is fed through the batcher into the annular groove of the rotating mold wheel and solidifies to contact with the stationary part of the container, formed at the interface of the groove with the arcuate segment (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…As studies of the methods of continuous extrusion of metals have shown [15][16][17][18][19][20][21][22][23][24], their use significantly increases the efficiency of the production of profiles from non-ferrous metals. One of the promising directions in the development of these technologies is the combination of continuous casting with extrusion on a Conform installation with a horizontal carousel mold [21][22][23][24][25][26]. During the operation of the installation, the metal melt is fed through the batcher into the annular groove of the rotating mold wheel and solidifies to contact with the stationary part of the container, formed at the interface of the groove with the arcuate segment (Fig.…”
Section: Introductionmentioning
confidence: 99%